4
$\begingroup$

How do I determine the limit as $x$ approaches zero of $$\frac{(x+1)\cos(\ln x^2)}{\sqrt{x^2+2}}$$ using the Squeeze Theorem. My suspicion is that it oscillates infinitely often and therefore doesn't have a limit but I don't know how to prove or explain it. What role would the squeeze theorem have in this though?

$\endgroup$
  • 2
    $\begingroup$ The squeeze theorem doesn't apply! I suspected whoever suggested that to you mistakenly assumed that $\frac{x+1}{\sqrt{x^2+2}} \to 0$. $\endgroup$ – Hurkyl Mar 24 '18 at 14:42
  • 1
    $\begingroup$ "it oscillates infinitely often and therefore doesn't have a limit" -- the use of the word "therefore" is misplaced. The expression $x \sin(1/x)$ also oscillates infinitely often as it approaches $0$ but it does have a limit. Oscillations can be damped. $\endgroup$ – John Coleman Mar 24 '18 at 18:47
  • $\begingroup$ @Tightrope Please remember that you can choose an answer among the given if the OP is solved, more details here meta.stackexchange.com/questions/5234/… $\endgroup$ – gimusi Mar 27 '18 at 14:09
4
$\begingroup$

Consider the sequences $\{x_k\}$ and $\{y_k\}$ given by $$x_k:=\exp(-\pi(2k+1)/2)\hspace{0.2cm}\text{and}\hspace{0.2cm}y_k:=\exp(-\pi k)$$ Then we get respectively $$\lim_{k\to\infty}\frac{(x_k+1)\cos\ln x^2_k}{\sqrt{x^2_k+2}}=\lim_{k\to\infty}\frac{(e^{-\pi(2k+1)/2}+1)\cos\ln e^{-\pi(2k+1)}}{\sqrt{ e^{-\pi(2k+1)}+2}}\\=\lim_{k\to\infty}\frac{(e^{-\pi(2k+1)/2}+1)\cos(-\pi(2k+1))}{\sqrt{ e^{-\pi(2k+1)}+2}}=-\lim_{k\to\infty}\frac{e^{-\pi(2k+1)/2}+1}{\sqrt{ e^{-\pi(2k+1)}+2}}=-\frac{1}{\sqrt{2}}$$ Similar calculations show that $$\lim_{k\to\infty}\frac{(y_k+1)\cos\ln y^2_k}{\sqrt{y^2_k+2}}=\frac{1}{\sqrt{2}}$$ Hence limit does not exist.

$\endgroup$
  • $\begingroup$ very nice proof ;) $\endgroup$ – gimusi Mar 24 '18 at 15:00
4
$\begingroup$

Yes it oscillates indeed note that

$$-\frac{(x+1)}{\sqrt{x^2+2}}\le \frac{(x+1)\cos(\ln(x^2))}{\sqrt{x^2+2}}\le \frac{(x+1)}{\sqrt{x^2+2}}$$

and

$$\frac{x+1}{\sqrt{x^2+2}}\to \frac{\sqrt 2}2$$

it can be proved assuming for $k\to -\infty$

  • $x_k=\sqrt{e^{2k\pi}}\to 0\implies f(x_k)\to \frac{\sqrt 2}2$
  • $y_k=\sqrt{e^{k\pi}}\to 0 \implies f(y_k)\to -\frac{\sqrt 2}2$
$\endgroup$
  • $\begingroup$ Why does (x+1)/sqrt(x^2+2) > sqrt(2)/2? $\endgroup$ – Tightrope Mar 24 '18 at 15:03
  • $\begingroup$ @Tightrope simply by plugging in x=0 since the function is continuos at x=0 $\endgroup$ – gimusi Mar 24 '18 at 15:07
  • $\begingroup$ doesn't (0+1)/sqrt(0 +2) = 1/sqrt(2)? $\endgroup$ – Tightrope Mar 24 '18 at 15:09
  • $\begingroup$ @Tightrope $1/\sqrt{2}=\sqrt{2}/2$. $\endgroup$ – Taneli Huuskonen Mar 24 '18 at 16:31
  • $\begingroup$ Oh yes sorry I didn’t received the notification for this last request of clarification, it is as Taneli explained of course! $\endgroup$ – gimusi Mar 24 '18 at 16:33
1
$\begingroup$

Here's an argument that avoids unnecessary computations. Note that the limit

$$\lim_{x \to 0} \frac{x+1}{\sqrt{x^2+2}} = \frac{1}{\sqrt{2}}$$

exists and is nonzero. hence

$$\left[ \lim_{x \to 0} \frac{x+1}{\sqrt{x^2+2}} \cdot \cos \ln(x^2) \right] \text{ exists} \iff \left[ \lim_{x \to 0} \cos \ln(x^2) \right] \text{ exists}.$$

Now let $f(x) = \cos \ln( x^2 ).$ For any $\delta > 0$ we have that

$$f \big[ (-\delta, \delta) \setminus \{ 0 \} \big] = \cos\left[ \ln \big[ (0, \delta^2) \big] \right] = \cos \big[ (-\infty, 2 \ln \delta ) \big] = [-1, 1],$$

hence the limit does not exist, for if it existed and were equal to $g \in \mathbb{R}$, then there would exist a $\delta > 0$ such that

$$f \big[ (-\delta, \delta) \setminus \{ 0 \} \big] \subseteq \left(g-\frac{1}{100}, g+\frac{1}{100} \right)$$

while clearly $[-1, 1] \not \subseteq \left(g-\frac{1}{100}, g+\frac{1}{100} \right)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.